KEBIJAKAN RESTRUKTURISASI PERUSAHAAN ASURANSI (Faculty of Law, University of Palembang, 2022)
The insurance company restructuring policy in the implementation of insurance business in Indonesia relies on the provisions in Article 11 of Law Number 40 of 2014 concerning Insurance in which an insurance company is required to implement good corporate governance. Based on the insurance business law, the regulation and supervision of activities is carried out by the Financial Services Authority. The restructuring of PT Asuransi Jiwasraya (Persero) is further regulated in OJK Regulation Number 71/POJK.05/2016 concerning the Financial Health of Insurance and Reinsurance Companies.